DYNAMICS OF ORGANIC MATTER UNDER THE AFFORESTATION OF THE FORMER AGRICULTURAL SOD-PODZOLIC SOILS - E. B. Taller; Z. S. Artemyeva; N. P. Kirillova; N. N. Danchenko (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
The dynamics of the organic matter of the chronosequence of sod-podzolic soils in the process of reforestation has been investigated using the granulo-densitometric fractionation.The objects of research were sod-podzolic soils of the chronosequence of abandoned areas, including the main stages of the development of secondary succession: from overgrowing by grass vegetation to zonal spruce forests of the specially protected natural territory of the Central Forest State Natural Biosphere Reserve. In the first 20–25 years after the reduction of agrocenosis, degradation changes of the humus state of sod-podzolic soils were observed, due to the lack of agrotechnological treatments and the lack of fresh organic matter (OM) of cultivated plants. It is shown that only after 50 years functioning in the reservoir regime, the qualitative and quantitative indicators of organic matter of sod-podzolic soils begin to approach those of spruce forests of different species composition over 100 years old. This is manifested in an increase in the amount of discrete OM, the level of carbon accumulation of this fraction of OM in the soil and the value of its share in the total carbon accumulation in the soil.